Effet In Vivo De Newbouldia laevis (Bignoniaceae) Sur Des Strongles Gastro-Intestinaux Des Moutons - Pascal, Olounladé Abiodoun; Eloi, Attakpa Yatchégnon; Bertrand, Azando Erick Virgile; Sylvie, Hounzangbé – Adoté Mawulé; Hervé, Hoste (European Scientific Journal, ESJ, 2017)
The in vivo evaluation of the effectiveness of pests leaves Newbouldia laevis (Bignoniaceae) was tested on gastrointestinal strongyles of Djallonké infested lambs naturally or artificially with larvae of Haemonchus contortus and Trichostrongylus colubriformis. In a controlled environment, the trial involved 15 lambs artificially infected and naturally infected some 14 was treated with the powder of N. laevis (1.6 g / kg BW). The parasitic balance sheet revealed that N. laevis limited larval Trichostrongylus installation colubriformis (P = 0.01), whereas it had no effect on the larvae of H. contortus after artificial infestation. Following natural infection, this plant has limited (P = 0.08) to the population of H. contortus adults was reduced by 55% in abomasum the experimental animals; this reduction is only 19% on the viability of adult worms of T. colubriformis (P> 0.05). However, N. laevis did not affect prolificacy to H. contortus females; but it has reduced by 11% T. colubriformis. Uncontrolled environment in a first trial, 16 animals were treated with 2 doses (3.2 or 4.8 g / kg BW) of dry powdered leaves. In a second test, the fresh leaves of N. laevis were proposed ad libitum consumption three times a week for 45 days. The results show that leaves N. laevis significantly reduced (P <0.05) excretion of gastrointestinal strongyles eggs (80-90%) in Djallonké lambs naturally infected regardless of the dose.